Permian endemic bivalves of the Irati anoxic event, Parana Basin, Brazil: Taphonomical, paleogeographical and evolutionary implications - Matos, Suzana Aparecida; Warren, Lucas Verissimo [UNESP]; Varejao, Filipe Giovanini [UNESP]; Assine, Mario Luis [UNESP]; Simoes, Marcello Guimaraes [UNESP] (Elsevier B.V., 2017)
Anoxic to dysoxic conditions must have existed in the Parana Basin during the deposition of the Permian oil-bearing shales of the Irati Formation, reflecting the marine isolation of the basin from the Panthalassic Ocean. In this environment, benthic invertebrates are extremely rare, in contrast to the overlying Serra Alta and Teresina formations, which were deposited in dysoxic/oxic waters, respectively. Hence, the abundant shallow-burrowing, endemic bivalves recorded in the shales of the basal portion of the Irati Formation are one of the most distinctive features of this stratigraphic interval. Their preservation in offshore deposits is, however, a product of storm flows in shallow waters that swept the shells to distal settings. Subsequently, these were sorted by long-lasting shelf currents that produced dense (2-5 shells/20 cm(2)) pavements in which shells in a hydrodynamically stable posture (convex-up) predominate, forming thin, complex shell concentrations despite their simple internal stratigraphy. The new data presented here have important paleoecologic, paleogeographic and evolutionary implications and indicate that (a) during the deposition of the oil-rich shales of the Irati Formation, numerous benthic bivalves thrived in the contemporary shallow-water bottoms of the Parana Basin; (b) the mono- to paucispecific nature of the studied shell-rich pavements is, in part, due to hydrologic shell transport; and (c) restricted connections to open ocean waters (Panthalassa) existed during Irati times. Therefore, the origin of the endemic Passa Dois molluscan fauna occurred somewhere between the interval represented by the underlying Palermo Formation and the basal portion of the Irati Formation. Finally, these endemic bivalves appeared at least-10 million years earlier than previously thought. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Anoxic crisis; Black shales; Endemic bivalves; Allochthonous shells; Permian; Southern Gondwana